AN ERROR ANALYSIS OF INDONESIAN-ENGLISH TRANSLATION - Prayuda, Meikardo Samuel (Kairos English Language Teaching Journal, 2020)
This thesis was purposely made to identify error analysis of Indonesian – English translation of news item text translation made by English Department students of FKIP Nommensen University. The result of this research was there were 4 translation errors made by the students in their Indonesian – English news item translation by considering the cohesive devices. The translation errors were in repetition device, conjunction device, reference device, and synonymy device. This result showed that the dominant translation error was dominated by the repetition translation error and synonymy translation error. The result of this research proved that the students had problems in translating.